The Criminal Law and the Civil Code in Day-to-Day Employee Relations - Buchanan, Erskine; Cutler, Philip; Renault, Paul-F. (Relations industrielles / Industrial Relations, 1959)
SummaryThe following are excerpts of a panel discussion sponsored some months ago (October 24th, 1957) by the Employee Relations Section of The Montreal Board of Trade. The panelists were: Messrs. Erskine Buchanan, Philip Cutler and Paul F. Renault, barristers and solicitors. Here is what they had to say on the terminating of employees' services (Mr. Buchanan), other aspects of the Civil Code concerning employee relations (Mr. Cutler), and the Criminal Law aspects of such relations (Mr. Renault).